علاقة الضغوط النفسية بالتوافق المهني لدى أساتذة التعليم المتوسط - سلاف ميسة; أمال باهي (جامعة الوادي - University of Eloued, 2025)
"هدفت الدراسة إلى التعرف على العلاقة بين الضغوط النفسية والتوافق المهني لدى أساتذة التعليم المتوسط ببلدية الوادي، كما تم استخدام المنهج الوصفي الارتباطي من أجل أغراض الدراسة، واستخدمنا في جمع البيانات مقياس الضغوط النفسية ""لعسكر وآخرون""(1986) ومقياس التوافق المهني للباحثين ""شيخاوي صلاح الدين"" و""شلابي وليد"" (2021) وطبقا على عينة بلغت (114) أستاذ وأستاذة من المتوسطات التالية مصباحي مصطفى، باهي علي، احمد التجاني ببلدية الوادي، وتم اختيارهم بالطريقة القصدية، وقد توصلت الدراسة إلى النتائج التالية: - توجد علاقة بين الضغوط النفسية والتوافق المهني لدى أساتذة التعليم المتوسط. - لا توجد فروق في الجنس من أساتذة التعليم المتوسط على مقياس التوافق المهني. - لا توجد فروق في الحالة الاجتماعية من أساتذة التعليم المتوسط على مقياس التوافق المهني. - لا توجد فروق في الأقدمية المهنية من أساتذة التعليم المتوسط على مقياس التوافق المهني. "the study aimed to imuestigat Lhe relatuoishifhetueen Pscuchological stress and proffssionalcompatilility Amoug middle school teachers in ELoued Lhedexriptue Correlatioal approach was also used for Lhepurposes Of Lhe study our use of data collection -Lhe psychological stress scale of AL Askar amd others(1986) amd Lhe propessional adjustment scoleof Resear chers sheikaur salah EL dine and shalal Walid (2021) according to a sample of 114 middle School teachers in the municipolity of ELoued they were chosen intentionally . there is acorrelation letween psychogieal stress and - Professioual compatilitiy among middle schoolteaehers - there are no statistically significant differences Attriluited to the gender varialle among middle school Teachers on the professional compatililiyy scale there are no statistically signifi cant differences attriluited to the varialle of social status of middle school teachers- On the professional compatilility scale -there are no statistically significant differences Attriluitalle to the varialle of proffessionalseniority Of professors.
مذكرة ماستر قسم علم النفس وعلوم التربية تخصص علم نفس المدرسي
Keywords: التوافق المهني; العلاقة بين الضغوط النفسية; Traditional Approval; Professional Compatibility